2014
DOI: 10.1155/2014/846486
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Skin-to-Skin Contact on Temperature and Breastfeeding Successfulness in Full-Term Newborns after Cesarean Delivery

Abstract: Background. The skin-to-skin contact (SSC) of mother and newborn is uncommon full-term newborns after delivering via cesarean section due to the possibility of hypothermia in the infants. The aim of this study was to compare mothers' and infant's temperatures after delivering via cesarean section. Material and Methods. In this randomized clinical trial, 90 infant/mothers dyads delivered via cesarean section were randomized to SSC (n = 46) and routine care (n = 44). In experimental group, skin-to-skin contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 12 publications
2
51
0
2
Order By: Relevance
“…22 For breastfeeding mother-infant dyads, SSC enhances the opportunity for an early first breastfeeding, which, in turn, leads to more readiness to breastfeed, an organized breastfeeding suckling pattern, and more success in exclusive and overall breastfeeding, 12,25,26 even after cesarean deliveries. 27 Further evidence shows a benefit for mothers after cesarean deliveries who practice SSC as soon as the mother is alert and responsive in increased breastfeeding initiation, decreased time to the first breastfeeding, reduced formula supplementation, and increased bonding and maternal satisfaction. 28 Increasing rates of breastfeeding ultimately have short-and long-term health benefits, such as decreased risk of infections, obesity, cancer, and sudden infant death syndrome.…”
Section: Evidence For Ssc and Rooming-inmentioning
confidence: 99%
“…22 For breastfeeding mother-infant dyads, SSC enhances the opportunity for an early first breastfeeding, which, in turn, leads to more readiness to breastfeed, an organized breastfeeding suckling pattern, and more success in exclusive and overall breastfeeding, 12,25,26 even after cesarean deliveries. 27 Further evidence shows a benefit for mothers after cesarean deliveries who practice SSC as soon as the mother is alert and responsive in increased breastfeeding initiation, decreased time to the first breastfeeding, reduced formula supplementation, and increased bonding and maternal satisfaction. 28 Increasing rates of breastfeeding ultimately have short-and long-term health benefits, such as decreased risk of infections, obesity, cancer, and sudden infant death syndrome.…”
Section: Evidence For Ssc and Rooming-inmentioning
confidence: 99%
“…Iranian researchers showed that early SSC has a significant and positive effect on early breastfeeding and its duration (25,(29)(30)(31)(32)(33)(34)43)Keshavarz et al reported that duration of exclusive breast feeding at six month of life was higher than that of RCs was (P < 0.05) (29). Kamalifard et al also showed that SSC has a significant positive effect on mean exclusive breastfeeding duration in infants receiving KMC (119.8 ± 13.2 vs 110.7 ± 24 days; P < 0.04) (42).…”
Section: Breastfeedingmentioning
confidence: 99%
“…Similar to the study of Moore and Anderson (59). Beiranvand et al and Ali-Akbar et al observed that early SSC after delivery had positive effects on full-term infant's pre-feeding behaviors (33,34). These behaviors have been considered effective on breast-feeding.…”
Section: Breastfeedingmentioning
confidence: 99%
“…The use of SSC after cesarean section was an unusual practice due to the risk of hypothermia. yet recent randomized clinical trials that examined the effect of SSC after cesarean section concluded that SSC doesn't increase the risk of hypothermia [35,36].…”
Section: Skin-to-skin Contact (Ssc)mentioning
confidence: 99%
“…The use of SSC after cesarean section was an unusual practice due to the risk of hypothermia. yet recent randomized clinical trials that examined the effect of SSC after cesarean section concluded that SSC doesn't increase the risk of hypothermia [35,36].Neonates accompanied by health care professionals such as doctors and nurses have a poorer outcome than those who are accompanied by their parents during transportation from delivery room to NICU [11]. Additionally, A randomized controlled trial that compares between the effect of ssc and conventional incubator on physiological stabilization revealed the following stabilization scores: 77.11 for SSC versus 74.23 for incubator, mean difference 2.88 (95% CI: 0.3-5.46, p = 0.031).…”
mentioning
confidence: 99%